Rapid and scalable assembly of firefly luciferase substrates - McCutcheon, David C. (Org Biomol Chem, 2015)
Bioluminescence imaging with luciferase-luciferin pairs is a popular method for visualizing biological processes in vivo. Unfortunately, most luciferins are difficult to access and remain prohibitively expensive for some imaging applications. Here we report cost-effective and efficient syntheses of D-luciferin and 6′-aminoluciferin, two widely used bioluminescent substrates. Our approach employs inexpensive anilines and Appel's salt to generate the luciferin cores in a single pot. Additionally, the syntheses are scalable and can provide multi-gram quantities of both substrates. The streamlined production and improved accessibility of luciferin reagents will bolster in vivo imaging efforts.